INTERTEKSTUALITAS KISAH NABI DAUD MENYUSURI NARASI AL-QUR’AN DAN ALKITAB DENGAN TEORI JULIA KRISTEVA - Didik Harianto (Yayasan Baitul Hikmah al-Zain, 2026)
This study responds to claims that the Qur'an is influenced by the Bible, particularly due to thematic parallels between the two. The story of Prophet David in both scriptures features four shared themes: his role as a divinely chosen leader (khalifah), his victory over enemies (Jalut/Goliath), his deep connection with God through praise (glorification/psalms), and his trials followed by repentance. Using qualitative library research, data are drawn from the official Indonesian Qur'an translation, the Bible via AlkitabSABDA, tafsir works, academic journals, and other relevant sources. The study finds that although thematic similarities exist, fundamental differences remain—especially the Qur'an’s emphasis on David’s prophethood and infallibility, which the Bible does not portray. Through an intertextual approach based on haplology and modification, this research shows that the Qur'an reshapes the David narrative with a distinctive moral focus. The story is presented in a way that maintains its core message while directing readers to the ethical wisdom it carries, affirming the Qur'an’s function as muhaimin (guardian and criterion) over earlier scriptures.